Nano-Medicine for Treatment of Tuberculosis, Promising Approaches Against Antimicrobial Resistance - Mobed, Ahmad; Alivirdiloo, Vahid; Gholami, Sarah; Moshari, Amirreza; Mousavizade, Azamsadat; Naderian, Ramtin; Ghazi, Farhood (Current microbiology, 2024)
Even though the number of effective anti-tuberculosis or anti-mycobacterial agents is increasing, a large number of patients experience severe side effects as a result of these drugs. This hurts the patients’ well-being and quality of life. Tumor cells that survive treatment modalities can become chemotherapy resistant at the molecular level. Furthermore, negative effects on normal cells occur concurrently. Strategies that minimize the negative effects on normal cells while efficiently targeting infected cells are required. Nanotherapies, according to recent research, may be one option in this direction. The present study differs from previously published review studies as it concentrates on examining the most recently developed nanoparticles for anti-mycobacterial purposes. Such novel approaches have the potential to reduce harmful side effects and improve patients’ health prognoses. Current paper provides a comprehensive analysis of recent advances in nanotherapy systems for the pulmonary delivery of anti-tuberculous drugs. In addition, to low-priced and convenient alternatives for pulmonary delivery, different types of NPs for oral and topical application were also deliberated and summarized in this review. Graphical Abstract